Managing Rock/Pop Tours: An Exploration of Logistical Dimensions - Paché, Gilles (Journal of Applied Business and Economics, 2023)
Rock/pop tours attract millions of fans each year around the world. But are they aware of the logistics involved in pulling off impressive shows? Indeed, for a touring to succeed, it requires the transport of many goods over long distances, with teams in charge of handling them, but also of assembling and disassembling the different elements of the stage structure every day. These teams must be fed and housed city after city, requiring efficient hospitality management. This is an essential supply chain dimension of rock/pop tours that is often ignored, even by graduate students, and yet it presents interesting business perspectives. The objective of this research note is to provide an overview of the critical aspects of the rock/pop tour logistics, both in terms of transport and handling, and the necessary planning of operations, which are very rarely studied in the supply chain management literature.